ENGLISH TEACHING MATERIALS SELECTION FOR DEAF IN A PUBLIC SCHOOL FOR STUDENTS WITH SPECIAL EDUCATION NEEDS (SEN) - Puadah, Annisa Syamrotul (2014)
The study conducted aimed to find out resources and teaching-learning aids of English instructional materials that were used by the teacher and also materials selection and adaptation which were conducted by the teacher who teaches DHH students. The study was conducted in public special school for DHH students in Bandung by taking only one experienced-teacher as the main participant. The study employed descriptive qualitative case study which used interview, questionnaire, and document analysis in collecting data. The findings reveal that the teacher used several resources for TL materials: available published materials, authentic materials, and created materials. In addition, although the teacher used many kinds of materials, the main and most beneficial materials are the visual and concrete ones because the students are visual learners. She also adapted the irrelevant and inappropriate materials by modifying them into the appropriate ones based on student's characteristics and needs. Penelitian ini bertujuan untuk meneliti sumber dan alat bantu pembelajaran bahasa Inggris dan pemilihan serta adaptasi materi ajar yang dilakukan oleh guru untuk siswa tuna rungu. Penelitian ini diadakan di SLB-B Negeri di Bandung dengan mengambil seorang guru berpengalaman menjadi partisipan utama. Penelitian ini menggunakan studi kasus deskriptif kualitatif dengan menggunakan wawancara, kuesioner, dan analisis dokumen dalam pengambilan data. Hasil penelitian menunjukkan bahwa guru menggunakan beberapa sumber dan alat bantu pembelajaran yaitu materi yang sudah diterbitkan, materi yang sudah diadaptasi, materi otentik, dan materi buatan. Selanjutnya walaupun guru menggunakan banyak macam materi ajar namun materi yang dianggap paling bermanfaat dan sesuai dengan siswa tunarungu adalah materi visual karena mereka adalah pembelajar visual. Guru mengadaptasi materi yang tidak sesuai dengan karakter siswa dengan cara memodifikasinya menjadi materi layak ajar berdasarkan karakteristik dan kebutuhan siswa.